2022
DOI: 10.1007/s10562-022-03967-8
|View full text |Cite|
|
Sign up to set email alerts
|

The Direct Synthesis of Hydrogen Peroxide Over Supported Pd-Based Catalysts: An Investigation into the Role of the Support and Secondary Metal Modifiers

Abstract: The direct synthesis of H2O2 from molecular H2 and O2 over Pd-based catalysts, prepared via an industrially relevant, excess chloride co-impregnation procedure is investigated. Initial studies into the well-established PdAu system demonstrated the key role of Pd: Au ratio on catalytic activity, under conditions that have previously been found to be optimal for H2O2 formation. Further investigations using the optimal Pd: Au ratio identified the role of the catalyst support in controlling particle size and Pd ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…However, this improvement in catalyst selectivity did not result in a concurrent increase in H 2 O 2 synthesis rates, with the 0.5%Pd–0.5%Au/TiO 2 (85 mol H 2 O 2 kg cat –1 h –1 ) and 1%Pd/TiO 2 (88 mol H 2 O 2 kg cat –1 h –1 ) catalysts offering comparable activities. While this may not have been expected given the large number of studies into PdAu systems, which have typically reported a significant improvement in H 2 O 2 synthesis upon formation of the alloy, this observation aligns well with our previous studies into identically prepared catalysts and is attributed to the application of a reductive heat treatment during catalyst preparation, and the resulting formation of nanoparticles consisting of a random alloy composition . Indeed, in many earlier studies, the use of an oxidative heat treatment, and the resulting formation of Au-core, Pd­(oxide)-shell nanoparticle morphologies has been shown to be key in achieving enhanced selectivity toward H 2 O 2 . , It is noteworthy that while the activity of the 0.5%Pd–0.5%Au/TiO 2 catalyst toward H 2 O 2 synthesis did not exceed that of the 1%Pd/TiO 2 catalyst, there was a considerable improvement compared to the 0.5%Pd/TiO 2 analogue (68 mol H 2 O 2 kg cat –1 h –1 ), which consists of an identical Pd loading.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, this improvement in catalyst selectivity did not result in a concurrent increase in H 2 O 2 synthesis rates, with the 0.5%Pd–0.5%Au/TiO 2 (85 mol H 2 O 2 kg cat –1 h –1 ) and 1%Pd/TiO 2 (88 mol H 2 O 2 kg cat –1 h –1 ) catalysts offering comparable activities. While this may not have been expected given the large number of studies into PdAu systems, which have typically reported a significant improvement in H 2 O 2 synthesis upon formation of the alloy, this observation aligns well with our previous studies into identically prepared catalysts and is attributed to the application of a reductive heat treatment during catalyst preparation, and the resulting formation of nanoparticles consisting of a random alloy composition . Indeed, in many earlier studies, the use of an oxidative heat treatment, and the resulting formation of Au-core, Pd­(oxide)-shell nanoparticle morphologies has been shown to be key in achieving enhanced selectivity toward H 2 O 2 . , It is noteworthy that while the activity of the 0.5%Pd–0.5%Au/TiO 2 catalyst toward H 2 O 2 synthesis did not exceed that of the 1%Pd/TiO 2 catalyst, there was a considerable improvement compared to the 0.5%Pd/TiO 2 analogue (68 mol H 2 O 2 kg cat –1 h –1 ), which consists of an identical Pd loading.…”
Section: Resultssupporting
confidence: 87%
“…In keeping with previous reports, 29−31 32 this observation aligns well with our previous studies into identically prepared catalysts and is attributed to the application of a reductive heat treatment during catalyst preparation, and the resulting formation of nanoparticles consisting of a random alloy composition. 33 Indeed, in many earlier studies, the use of an oxidative heat treatment, and the resulting formation of Au-core, Pd(oxide)-shell nanoparticle morphologies has been shown to be key in achieving enhanced selectivity toward H 2 O 2 . 34,35 It is noteworthy that while the activity of the 0.5%Pd−0.5%Au/TiO 2 catalyst toward H 2 O 2 synthesis did not exceed that of the 1%Pd/TiO 2 catalyst, there was a considerable improvement compared to the 0.5%Pd/ TiO 2 analogue (68 mol Hd 2 Od 2 kg cat −1 h −1 ), which consists of an identical Pd loading.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…H2O2 decomposition is catalyzed at two different pH values, 7 and 10, by our borohydride-stabilized Pt nanoparticles at 25°C. The rate of reaction is determined by acidified Ce(SO4)2 titrations, as has been utilized previously in the literature to measure H2O2 synthesis and decomposition rates [27,[45][46][47]. Further details of the titrations are included in Section 3.5.…”
Section: Catalytic Reaction Testingmentioning
confidence: 99%
“…The alloying of Pd with a range of secondary metals, [15][16][17][18] particularly Au, [19][20][21][22] has been extensively studied and demonstrated to improve catalytic reactivity and selectivity towards H 2 O 2 synthesis when studied under optimised reaction conditions. These enhancements are often attributed to the modification of Pd oxidation states and the disruption of contiguous Pd domains.…”
Section: Introductionmentioning
confidence: 99%